PENGARUH THIN CAPITALIZATION, INTENSITAS PERSEDIAAN, DAN LIKUIDITAS TERHADAP AGRESIVITAS PAJAK - Afifah Istiqomah; Sri Trisnaningsih (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
Tax aggression is a term that refers to the practice of reducing the tax burden in both legal and illegal ways. The purpose of this study is to examine and analyze the effects of tax aggressiveness on undercapitalization, insentisitas persediaan, and liquidity. This is a quantitative study that makes use of secondary data from financial statements. This study examines 30 food and beverage companies that were listed on the Indonesian Stock Exchange (IDX) between 2016 and 2020. The study sample was chosen through a targeted sampling procedure and then provided with 65 data points from 13 companies. Multiple regression equation analysis techniques were used to analyze the data. The findings indicate that undercapitalization, insentisitas persediaan, and liquidity have no effect on tax aggressiveness between 2016 and 2020. That is, whether a company is tax aggressive or not has no bearing on its decision to be tax aggressive. Keywords: Tax aggression, thin capitalization, inventory, liquidity